Hyperclycemia, Young Age, Altered Sleep Habits: The Three Shifting Paradigms of Coronary Artery Disease Risk Stratification (Ibrahim Medical College Journal, 2013)
The study was undertaken to estimate the risk factors age, gender, race, obesity (BMI), glycemic status (prediabetes, diabetes), exercise and psychosocial factors (sleep, sadness) related to coronary artery disease (CAD). The data set for this study is the National Health Interview Survey (NHIS), which is a large scale, cross sectional, voluntary, household interview survey maintaining data on health status, health care access and progress towards achieving the national health objectives in the USA. A total of 26,965 (male/female =55.8/ 44.2%) subjects were included in the study. Of them, 79.9% were less than 65 years of age. Regarding obesity, overweight, obese and morbid obese were 34.8, 17.3 and 11.0%, respectively. Sadness of any degree was reported in 28%. Sleep duration was found 9h/d in 9.7%. Heart disease was reported in 4.9%. About 10% were reported to have diabetes and 4.1% prediabetes. 40% of the respondents maintained exercise once per week and only 12.8% maintained 10 or more times per week. Logistic regression estimated that compared with the non-diabetics, the subjects with prediabetes (OR 3.27, 95% CI, 2.32-4.59) and diabetes (OR 6.44 95% CI, 5.21-7.96) had excess risk of CAD, more significant in the younger subjects (65y). The risk of CAD was found significant in both prediabetes (OR 2.47, 95% CI, 1.44-4.23) and diabetes (OR 3.03, 95% CI, 2.16-4.24) as compared with nondiabetic group who slept >9h a day. The subjects with prediabetes or diabetes had excess risk for CAD compared with the non-diabetic subjects, which was more marked in the younger people. Again, compared with the non-diabetic people, the subjects with prediabetes or diabetes, having less sleep or excess sleep, had excess risk for CAD. Further study may confirm our findings. DOI: http://dx.doi.org/10.3329/imcj.v6i2.14727 Ibrahim Med. Coll. J. 2012; 6(2): 39-45